Tratamiento informativo del tema ecológico-ambiental en los diarios la Prensa y los Andes de Riobamba, periodo marzo-agosto 2018”. - Villamarín Juelas, Tanya Maribel (2019)
The main objective of this research project is to analyze the information treatment of the ecological-environmental topic in the La Prensa and Los Andes newspapers of Riobamba, March-August 2018 period. This research is based on the theoretical framework used to develop basic concepts such as: Communication, journalism, printed media, information treatment, among others; and in the communication theories that complement this work, such as: the functionalist theory, the double flow of communication, the theory of the hypodermic needle, and more. The inductive-deductive method was used in the investigation since it allowed to examine the editorial content published by the printed media during the period mentioned above of inquiry; The study population was 265 people, and three journalists were interviewed. One of the results obtained through the surveys applied is that 92% of the Riobambeña population is interested in information regarding the ecological-environmental topic, but that there is only 5.92% total journalistic content published in the two local print media, these data are the result of the demographic review carried out in the Municipal Library of Riobamba. Finally, with all the qualitative and quantitative results achieved, the elaboration of a printed communication product in which the necessary information corresponding to the ecological-environmental theme is indicated, and thus to implement in some way the awareness in people and therefore to search improvement in the informative treatment by the printed media.